Óleos essenciais para controle de carrapatos: revisão das pesquisas com testes em condição de campo e avaliação de eficácia de combinações de carrapaticidas com (E)-cinamaldeído para controle de Rhipicephalus microplus - Gonzaga, Bruno César Ferreira (2022)
The Rhipicephalus microplus tick was originally found infesting ruminants in South Asia and transported on zebu cattle to other locations in the world. This arthropod causes direct damage to the hosts, being the biggest cause of economic losses in livestock worldwide. In Brazil, with 224.6 million cattle, estimates point to losses of more than 3 billion dollars annually. The control of this parasite is carried out almost exclusively with synthetic acaricides. However, the constant and sometimes incorrect and indiscriminate use of these products can accelerate the selection of resistant ticks. Research to develop technologies to control ticks has been carried out, such as the use of vaccines, biological control agents and essential oils (EOs). Cinnamon (Cinnamomum zeylanicum) EO and its derivative (E)-cinnamaldehyde have acaricides activities. Some EOs and compounds present in EOs (CEOs) showed good acaricide results, including the association between them and synthetic products in vitro and in vivo studies, but these studies are scarce. The present study reviewed the literature with EOs and CEOs for field and semi-field tick control between the years 1991 and 2021 and investigated the effect of the combination of (E)- cinnamaldehyde and amitraz in the laboratory and in the field to control R .microplus. Twentyeight studies were selected in the review, of which 53.6% were carried out in Brazil, 71% with the application of EOs and CEOs in animals and 29% in the environment. In these studies, the spray application method was the most used (75%). The bovine species was the most studied (70%) and the tick R. microplus the most researched (46.4%). From this field and semi-field review, we realized the still limited number of articles evaluating the use of EOs and CEOs, and further studies under these conditions are needed to assess the real potential of these substances for tick control. In this sense, some aspects need to be prioritized: the characterization of the EOs, the standardization of the methodologies used in the efficacy evaluation tests, the use of EOs and COEs combined with synthetic acaricides (looking for synergistic interactions), the development of formulations and the evaluation of the application safety for animals, humans and environment. In vitro tests were carried out with 116 populations of ticks from all regions of Brazil, with 14 synthetic products, and those with 50-80% efficacy was chosen, having only one active ingredient. Subsequently, the products based on amitraz and chlorfenvinphos were tested in binary combinations with (E)-cinnamaldehyde in a tick strain, called CM strain, which showed better results for amitraz. The best association of (E)-cinnamaldehyde and amitraz was used in pharmacotechnical studies for the development and characterization of formulations, evaluating the in vitro and in vivo efficacy to control R. microplus infestations and clinical safety for cattle. The approach of combining this CEO and the synthetic product improved the effectiveness of the latter (reaching 86%) in engorged females (in vitro), but in the field study with application on animals, (E)-cinnamaldehyde caused intoxication in cattle. Future research, seeking to reduce the toxicity of formulations with (E)-cinnamaldehyde, deserves to be investigated.